2016
DOI: 10.1016/j.jbusres.2015.07.036
|View full text |Cite
|
Sign up to set email alerts
|

Strategy narratives and wellbeing challenges: The role of everyday self-presentation

Abstract: Through the lens of consumption, this study contributes to understanding the link between self and everyday interactions by identifying and developing a typology of wellbeing challenges and how these are managed in a variety of social contexts. Fifteen phenomenological interviews revealed a series of strategy narratives through which individuals pursue wellbeing within their web of social encounters. These strategy narratives combine in a series of pathways that range from harmonious (e.g., enhancement) to inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 63 publications
(72 reference statements)
2
21
0
Order By: Relevance
“…Our study did not explain the impression motivation behind the effect, such as selfpresentation (Liu et al, 2016). Instead, we used CLT to illustrate the association between temporal focus and the consumer's self.…”
Section: Limitations and Future Directionsmentioning
confidence: 92%
“…Our study did not explain the impression motivation behind the effect, such as selfpresentation (Liu et al, 2016). Instead, we used CLT to illustrate the association between temporal focus and the consumer's self.…”
Section: Limitations and Future Directionsmentioning
confidence: 92%
“…Both Merleau-Ponty and extant consumer research on personal grooming have been concerned with understanding the self-body unity (Belk & Costa, 1998;Entwistle, 2000Entwistle, , 2015Kinnunen, 2010;Liu, Keeling, & Hogg, 2016;McAlexander & Schouten, 1989;Ourahmoune, 2012). In terms of male grooming, Rinallo (2007), for example, found that heterosexual men rely on available cultural discourses to determine do's and don'ts when it comes to fashion and physical appearance.…”
mentioning
confidence: 99%
“…In the consumption setting, earlier studies have established the importance of cultivating specific self-presentations through pesonal adornment as a means of achieving a variety of identity and/or relationship goals (Askegaard, Gertsen, & Langer, 2002;Russell W. Belk, 2003;Liu et al, 2016;McAlexander & Schouten, 1989;Ruvio & Belk, 2018;Schouten, 1991). McAlexander and Schouten (1989) show how hairstyling could help consumers facilitate identity transition.…”
Section: Consumers and Their Self-presentationmentioning
confidence: 99%